Analisis Pemasaran Buah Naga (Hylocereus Polirhizus) Studi Kasus: Desa Teratak Nagodang Kecamatan Ujung Padang Kabupaten Simalungun - Fadila, Putri; Tantawi, Ahmad Rafiqi; Siregar, Rahma Sari (Universitas Medan Area, 2024)
This article aims to determine the marketing channels for dragon fruit and the efficiency of dragon fruit marketing channels in Taratak NagodangVillage, Ujung Padang District, Simalungun Regency. The Problem focuses on marketing channels and the efficiency of dragon fruit marketing channels. The theoretical references used in reviewing this article are Kotler’s (2015) theory for marketing channels and Su’udi’s (2018) theory with marketing margins. This research is qualitative and quantitative descriptive research. The research sample for dragon fruit farmers used random sampling, while the sample for traders used the census method, and the consumer sample used the incidental sampling method. The results of the research show that there is one level of the channel formed in the marketing of dragon fruit in Taratak Nagodang Village, Ujung Padang District, Simalungun Regency, namely from farmers to collecting traders, then wholesalers, retailers, and finally external consumers. Taratak Nagodang Village is the closest city to Batu Bara and Meranti. The lowest marketing margin for dragon fruit is with a margin percentage of 28% for collecting institutions and for all efficient marketing institutions with a value of 48%. Wholesalers with an efficiency value of 7% are the most efficient institutions.